Drought Vulnerability Index (DVI) in Attica Region, Greece using climate models upon the climate scenarios A1B and A2. ORIENTGATE Technical Report - A. Krzic; V. Djurdjevic; Papadimos, D.; S. Katsavouni (Republic Hydrometeorological Service of Serbia (RHMSS), 2017)
The study was commissioned within the preparation of the River Basin Management Plan of Attica Water District (Ministry of Environment 2013). Its main purpose was to: a) quantify the effects of drought and water shortage in the water district of Attica, b) to examine possible methodologies for predicting future incidents and c) to propose remedies for various levels of risk. This essay aims to strengthen the effectiveness of the above "Drought and Water shortage Management Plan" of the Attica Water District, by enhancing the forecasting process of future drought incidents.